2015
DOI: 10.1097/tp.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

Tumors With Intrahepatic Bile Duct Differentiation in Cirrhosis

Abstract: This series showed that patients with CCA within Milan criteria may be able to achieve acceptable long-term post-LT survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 43 publications
2
35
0
6
Order By: Relevance
“…We were able to identify 48 patients who had only iCCA at explant, representing by far the largest cohort of patients with this characteristic published to date. (6,8,(12)(13)(14)(15)(16) Also, we were able to almost duplicate the number of patients in the very early iCCA group from the previous Spanish multicenter experience, (8) adding value to the current work.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We were able to identify 48 patients who had only iCCA at explant, representing by far the largest cohort of patients with this characteristic published to date. (6,8,(12)(13)(14)(15)(16) Also, we were able to almost duplicate the number of patients in the very early iCCA group from the previous Spanish multicenter experience, (8) adding value to the current work.…”
Section: Discussionmentioning
confidence: 64%
“…Most of these patients had lesions that were misdiagnosed—in the preoperative setting—as being HCC; but some patients were transplanted for decompensated cirrhosis, and the tumors were incidentally found. We were able to identify 48 patients who had only iCCA at explant, representing by far the largest cohort of patients with this characteristic published to date . Also, we were able to almost duplicate the number of patients in the very early iCCA group from the previous Spanish multicenter experience, adding value to the current work.…”
Section: Discussionmentioning
confidence: 73%
“…When compared with the LR group, patients who underwent LT were younger (59 versus 63 [48-80] years; P = 0.03) and had a lower BMI (27 versus 29 [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] kg/m 2 ; P = 0.046; Table 1). A significantly higher rate of diabetes was seen in transplanted patients (23 [47%] versus 6 [23%]; P = 0.04), and they had a significantly higher MELD score (12 versus 7 [6][7][8][9][10][11][12][13][14]; P < 0.001). The median time elapsing between tumor diagnosis and liver surgery was significantly different for LT patients (394 versus 131 [5-864] days; P = 0.005).…”
Section: Lr Compared With Ltmentioning
confidence: 99%
“…(8,9) However, recent reports have demonstrated that LT is appropriate in a well-selected group of patients with cirrhosis, with 5-year survival rates ranging from 57% to 73%. (10,11) It appears that patients with very early iCCA, defined by a tumor size ≤2 cm, can be safely transplanted and achieve a 5-year actuarial survival rate of 65%. (12) Indeed, the radiological detection and characterization of small tumors before surgery are extremely challenging, particularly in a cirrhotic liver, as the classic enhancement patterns of iCCA become less reliable with lesions ≤2 cm.…”
mentioning
confidence: 99%
See 1 more Smart Citation